WZCollections / Puteri Nur Najwa Ab Halim - Ab Halim, Puteri Nur Najwa (2021)
WZCollections is a sole proprietorship business that offers hijab as one of the essentials in fashions for Muslim women after seeing online business opportunities in Selangor Darul Ehsan when demand arises. The headquarters of this business located in Batang Kali, Selangor and it is owned by Puteri Nur Najwa binti Ab Halim, a student of Bachelor’s in Science (Hons.) Tourism Management from Mara University of Technology (UiTM), Puncak Alam campus. WZCollections serves the market by supplying consumers with wants and needs since it has shown that buyers hit the shawl trend, which also benefits ironless and easy to style. The business also provided free delivery on specific prices to maintain the client relationship. WZCollection’s marketing approach is to focus entirely on low price, and highquality materials, which are in high demand among today's youth. Selling scarves has long been a market necessity since they are classified as being one of Muslim women's requirements. Batang Kali is a location where people are so concerned about their careers and everyday life that they have no time to shop. The head scarf is worn by nearly half of Muslim women based on article by The New Yorker in an interview with Vivy Yusof. This is thus viewed as a chance since the people of Muslim citizens are the most widespread and growing religion in Malaysia. Finally, as a start-up business, WZCollections continues to work and divides up the specialized task of supporting the packaging and supply services. This business is expecting to hire more employee in the next year when their finances are secured as this will help WZCollectionsto be more effective and efficient as the business need the helping hands, especially on the photography. The business also plans to improve its customer base and upgrade developed ones via social media.